Preventive Nutrition The Comprehensive Guide for Health Professionals - Bendich, Adrianne.; Bendich, Adrianne.; Deckelbaum, Richhard J.; Deckelbaum, Richhard J. (Nutrition and Health, 2005)
In this major revision and expansion of a highly respected reference work, the authors have created the most comprehensive and up-to-date review of the nutritional strategies available for the prevention of disease and the promotion of health through nutrition. This new edition combines fully updated versions of the best chapters of the first two editions with updated critical chapters from the much-praised Primary and Secondary Preventive Nutrition, and adds 16 new chapters. Here, practicing health professionals will find all new reviews of lycopene, tomatoes and prostate cancer, soy and cancer prevention; the effects of dietary supplement use on prescription drugs, osteoarthritis, osteoporosis, and cardiovascular disease; balanced, data-driven reviews of the effects of antioxidant supplements on health outcomes, and more. By synthesizing the latest data and integrating it into the broad body of existing information, this book provides in-depth guidance on nutrition and the prevention of cancer, cardiovascular disease, bone diseases, obesity, and diabetes, and on achieving optimal pregnancies and birth outcomes. Of special interest are the new chapters as well as the extensively revised chapters on drug-nutrient interactions, health economics, nutraceuticals, Food and Drug Administration regulations for supplements, carotenoids, the elderly, children, diet and cancer risk, obesity as a chronic disease, diabetes, and immune function. Key point summaries and clinical recommendations are clearly provided at the end of each chapter to highlight critical lessons for the reader. Comprehensive, authoritative, and readily accessible, Preventive Nutrition: The Comprehensive Guide for Health Professionals,Third Edition offers physicians, nutritionists, dentists, pharmacists, dieticians, health educators, policymakers, and research investigators a benchmark integration of the best available data on the role of nutrition in health. Unique in scope, size (over 900 pages), and detail, it demonstrates that many of the major diseases affecting middle-aged adults can be delayed, if not prevented, with simple nutritional approaches.